The Current Status of Autotitrating Continuous Positive Airway Pressure Systems in the Management of Obstructive Sleep Apnea - David Hailey; Philip Jacobs; Irvin Mayers; Shaila Mensinkai (Canadian Respiratory Journal)
BACKGROUND: Autotitrating continuous positive airway pressure (APAP) devices have the potential to address some of the disadvantages of titration and treatment with conventional continuous positive airway pressure (CPAP). Information on the performance of APAP in clinical use is still comparatively limited.